INDICATIVE PEDAGOGICAL CONDITIONS AND METHODS OF FORMATION OF COMMUNICATIVE COMPETENCE OF FUTURE TEACHERS OF MUSIC ART - Гурбіч, С.О.; Брежнєва, С.Б. (SWorldJournal, 2022)
The problem of the formation of the communicative competence in the future teachers of musical art has been actualized in the publication. The authors understand the communicative competence as the ability of the person to interact successfully and effect